Patterns of stress coping and depression among patients with head and neck cancer: A Japanese cross‐sectional study. Issue 2 (27th September 2017) - Ichikura, Kanako; Yamashita, Aya; Sugimoto, Taro; Kishimoto, Seiji; Matsushima, Eisuke
Abstract: Objective: Patients with head and neck cancer (HNC) experience many stressful problems with breathing, eating, swallowing, and/or speaking. The aim of this study was to (a) identify the clusters of HNC patients based on their stress coping strategies and (b) evaluate the differences in clinical data and depression among the identified HNC patients' coping clusters. Methods: We conducted a single‐center, cross‐sectional study with self‐completed questionnaires for patients with HNC between April and August 2013. We measured stress coping (an abbreviated version of the COPE Inventory: Brief COPE) and depression (the Japanese version of the Beck Depression Inventory‐II: BDI‐II). Results: Of the 116 patients who completed all the questionnaires, 81 (69.8%) participants were 60 to 79 years old and 105 (90.5%) were men. Cluster analysis based on the standardized z score of Brief COPE showed that patients were classified into 3 clusters, labeled "dependent coping, " "problem‐focused coping, " and "resigned coping." The ANOVA revealed that depression (BDI score) was significantly higher in the dependent‐coping cluster compared with the problem‐focused coping. Conclusions: This study indicates that patients with a dependent‐coping pattern may account for the largest HNC population and are likely to suffer from depression. Dependent coping includes smoking, drinking, seeking support, or engaging self‐distraction. In the future, we should develop psychological intervention programs focused on coping strategies and enhancement of the support system for patients with HNC.